2020
DOI: 10.3390/safety6040055
|View full text |Cite
|
Sign up to set email alerts
|

On Driver Behavior Recognition for Increased Safety: A Roadmap

Abstract: Advanced Driver-Assistance Systems (ADASs) are used for increasing safety in the automotive domain, yet current ADASs notably operate without taking into account drivers’ states, e.g., whether she/he is emotionally apt to drive. In this paper, we first review the state-of-the-art of emotional and cognitive analysis for ADAS: we consider psychological models, the sensors needed for capturing physiological signals, and the typical algorithms used for human emotion classification. Our investigation highlights a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 139 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…In this case, similarly to scenarios where UAVs should interact with each other, on the ground (i.e., along roads and highways) there may be the need to collect data (e.g., for monitoring purposes) directly from the vehicle and the driver by relying on the MIG. This would involve (i) the interaction of the MIG with the vehicle's On Board Unit (OBU) for diagnostic information retrieval, through wireless or wired communication interfaces, as well as (ii) data collection at the MIG from additional equipment and devices installed inside the vehicle's cabin (e.g., driver's smartphone and wearables for monitoring his/her stress levels [30]), through wireless communication interfaces.…”
Section: Mig Architecturementioning
confidence: 99%
“…In this case, similarly to scenarios where UAVs should interact with each other, on the ground (i.e., along roads and highways) there may be the need to collect data (e.g., for monitoring purposes) directly from the vehicle and the driver by relying on the MIG. This would involve (i) the interaction of the MIG with the vehicle's On Board Unit (OBU) for diagnostic information retrieval, through wireless or wired communication interfaces, as well as (ii) data collection at the MIG from additional equipment and devices installed inside the vehicle's cabin (e.g., driver's smartphone and wearables for monitoring his/her stress levels [30]), through wireless communication interfaces.…”
Section: Mig Architecturementioning
confidence: 99%
“…Using an advanced driver assistance system for increasing safety was proposed in [26]. Driving security and quality for both passengers and drivers are ensured in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…The study conducts literature reviews on the four dimensions by gathering and analyzing the documents as listed in Table 1 [11][12][13][14][15][16][17][18][19][20]. The literature reviews have found that a driver is influenced by the behaviors of other drivers under complex traffic situations, time pressure or at-risk events as they are causes of frustration in driving [21]. Regarding the driver characteristics that can be extracted from their behaviors [22], the researchers analyze the Driver Behavior Questionnaire on the correlation and risk of accidents on a tollway [23][24][25][26][27][28][29] from the variables such as abnormality, mistakes and rule violations [30].…”
Section: Introductionmentioning
confidence: 99%